PEMASARAN PRODUK OLAHAN IKAN LAUT UKM KENJERAN SURABAYA BERBASIS MARKETING MIX SYARIAH - Siti Maro'ah (BALANCE: Economic, Business, Management and Accounting Journal, 2016)
ABSTRACTMarketing advantage can be achieved by considering 7 (seven) variables of "Marketing Mix" consisting of Product, Price, Place (Distibution), Promotion, People, Process, and Physical Evidence. Given 87.18% of the Indonesian population embraced Islam (Shaw, 2006) it is very relevant when applied model of Sharia Marketing. Through Sharia Marketing Mix the whole process, both the creation process, the supply and the change of value (value), should not be in conflict with the Islamic muamalah and the principle of muamalah.The results showed that the processed fish products of UKM Kenjeran Surabaya fish depends on the catch of fishermen both in quantity and quality. The pricing is in agreement with the seller-buyer, and there is no element of usury. Distribution of product marketing is marketed in the surrounding area and serving orders. Promotion is done through exhibition when in village or neighborhood RT / RW held a celebration. Reasonable marketing service, with greetings, greetings, smiles, courtesy, and courtesy. The conventional marketing process has not yet paid attention to attractive product packaging and brand (brand) that can be known to the wider community. Physical proof of marketing is still used simple and simplistic recording.Keywords : SME, Product Marketing, Sharia Marketing MixCorrespondence to : siti.maro39ah@yahoo.com